Climate change and economic resilience through urban and cultural heritage: The case of emerging small island developing states economies - Zaheer Allam; David Jones (Economies, 2019)
While the topic of climate change is of global importance and has global consequences, the context is far more dangerous for emerging economies, including small island developing states (SIDS) and their coastal cities. The literature supports the need for robustness in infrastructural dimensions of such economies. However, the preparatory economic aspects have been overlooked in favour of post-impact disaster management studies by many countries. The latter studies have also focused upon the need for heavy financial investments without investigating solutions for economic strengthening of those economies including climate change mitigation and affordability. As such, emerging SIDS economies have struggled to meet these obligations from their internal finances that draw predominantly from tax revenue sources and foreign aid thereby often leading to increased debts contributing to economic austerity and decreasing liveability levels when repayment commitments fail. Public-private partnerships (PPP), another sought-after loan strategy, which often attracts foreign direct investment (FDI), can work if PPPs are carefully designed within strict public monitoring criteria. However, their applicability needs to be expanded to include the wider social strata of a city to ensure inclusivity and cohesiveness, and formulated to contribute to a wider urban regeneration agenda. This paper proposes a more inclusive framework bridging governance with drivers for sustainable development, using urban heritage and culture as a strategic thread for debt repayment and economic empowerment through PPP. This paper seeks to inform policymakers on sustainable pathways as it relates to SIDS cultural heritage conservation policies and practices towards better economic resilience in the wake of climate change.
Keywords: 330; climate change; debt; economic resilience; urban and cultural heritage; culture; sustainable development; small island developing states (SIDS)